CRITICAL TRADITION OF MEDIA CULTURE RESEARCH: THE FRANKFURT SCHOOL - Ороховська, Л. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article provided an analysis of the critical tradition of study of the influence of mass media on society on the example of the Frankfurt School and shows its importance for the formation of the modern media culture.